Reasons for Persistence of Dwelling Vulnerability to Chagas Disease (American Trypanosomiasis): A Qualitative Study in Northeastern Brazil - Taís F. Gomes, Francisca Samya S. Freitas, Claudia M. Bezerra, Marli M. Lima and Filipe A. Carvalho-Costa (World Health & Population, 2013)
Interaction between Chagas disease vectors and man is continuous in vulnerable dwellings, in which the vectors feed on man and find conditions for reproduction. This study explores factors that affect the choice of home construction methods in a rural community in Brazil, emphasizing the rationale for the persistence of dwelling vulnerability. Information on local resident perspectives regarding safety and home construction methods was gathered through domiciliary interviews with open questionnaires. The study revealed a large proportion of vulnerable mud huts, with others under construction. Insecurity over land tenure inhibits the construction of definitive houses. Mud homes are associated with greater structural stability. Cultural and economic factors have clearly been linked to the choice of method for home construction. The economic evolution of family conflicts with traditional aspects as well as the relative increased cost of the materials needed for mud house construction has not completely inhibited building with mud.
Keywords: Chagas Disease Brazil